Statistical inference in continuous time economic models - Bergstrom, A. R. (Amsterdam ; New York : North-Holland Pub. Co. ; American Elsevier Pub. Co., 1976)
The book consists of nine papers plus introduction, written by five people. The intended purpose of the various papers and hence of the book, has been stated by the editor as follows: 'The central idea underlying the methods developed in this book is that, since the variables that occur in most econometric models are the result of a large number of microeconomic decisions taken at different points of time, the prior restrictions [due to the theory] should be placed directly on the parameters of a continuous system, even though the variables are observed only at discrete intervals. The purpose of the book is to provide a body of statistical theory relating to the identification and estimation of the parameters of such models from discrete observations of the variables".
Includes bibliographical references and index.
rpm 04/04/2018
Loans
Keywords: Statistical inference; Mathematical statistics; Stochastic differential equations; Stochastic systems